Tirer le meilleur parti possible de l'initiative 'Tout sauf les armes' - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Lors de sa visite au Cambodge en février, le Commissaire...